Recruitment strategies and reach of a digital fall-prevention intervention for community-dwelling older adults. (September 2022) - Pettersson, Beatrice; Bajraktari, Saranda; Skelton, Dawn A; Zingmark, Magnus; Rosendahl, Erik; Lundin-Olsson, Lillemor; Sandlund, Marlene
Background: To have an impact on the population's health, preventive interventions have to reach a large proportion of the intended population. Digital solutions show potential for providing wider access to fall preventive exercise. However, there is a lack of knowledge about how to reach the target group. The aim of this study was to describe the recruitment process used in the Safe Step randomised controlled trial and the characteristics of the participants reached. Methods: Several recruitment methods, both digital and non-digital, were adopted to reach the intended sample size. Sociodemographic parameters from the baseline questionnaire were used to describe participant characteristics. The characteristics were also compared to a representative sample of older adults in the Swedish population. Results: In total, 1628 older adults were recruited. Social media proved to be the most successful recruitment strategy, through which 76% of the participants were recruited. The participants reached had a mean age of 75.9 years, lived in both urban and rural locations, were already frequent users of the Internet and applications (smartphone/tablet) (79.9%), had higher education (71.9%), and a large proportion were women (79.4%). In comparison with the general population participants in the Safe Step study were more highly educated ( p  < 0.001), women in the study more frequently lived alone ( p  < 0.001) and men more often reported poorer self-rated health ( p  = 0.04). Within the study, men reported a faster deteriorating balance ( p  = 0.003) and more prescribed medication ( p  < 0.001) than women. Conclusion: Recruitment via social media is a useful strategy for reaching older adults, especially women and frequent users of the Internet, for a fully self-managed and digital fall prevention exercise intervention. This study underlines that a range of interventions must be available to attract and suit older adults with different functional statuses and digital skills.